Fishing motivations and preferences of recreational anglers at pay-fishing ponds in Serdang, Selangor - Mohammad Saidi, Mohammad Nazrin (2018)
This study was conducted to understand the fishing motivations of anglers who fish at pay-fishing ponds in Serdang, Selangor. This study also tried to understand the basic socio-demographic backgrounds of those anglers and their preferences towards non-native fish species in Malaysia. A set of survey questionnaire was used to collect anglers data with a face-to-face sampling technique. A total of 100 pay-fishing pond anglers were taken part in this study, with 62.5% of response rate. Seventy-four percent of the anglers are Malay anglers (74.0%), and this was followed by Chinese (20.0%) and Indian anglers (6.0%). The highest age group was represented by age of 30 to 39 (46.7%) and were followed by age group of 40 to 49 (32.2%), 20 to 29 (15.6%), and 50 above (5.6%). Most of the anglers are self-employed (38.0%) and most of them have at least Diploma (37.0%). Seventy-five anglers are married (75.0%) while the rest are single. The results of this study revealed that the angler’s fishing motivations are varied. The highest fishing motivation placed by the pay-fishing pond anglers was ‘avoiding a moment from stress at work’ (4.49±0.54) while the lowest motivation was ‘failed to catch a fish’ (1.78±1.26). They also like to ‘spend time with friends’ (4.39±0.60), ‘fleeing from the bustle of the city’ (4.32±0.65), ‘master the technique of fishing’ (4.30±0.83), ‘enjoy the surrounding’ (4.20±0.67), ‘catch large and extraordinary fish’ (4.20±0.68), ‘spend time with family’ (4.12±0.91) ‘release all captured fish’ (4.03±4.1) and ‘catch as many fish possible’ (4.01±0.8). However, the results of motivations were found varied between different groups of anglers, based on their basic socio-demographic backgrounds. In terms of angler’s preferences towards the non-native species, most of the anglers preferred to catch kerapu (4.63±0.56), followed by siakap (4.59±0.53) and patin (4.26±0.85). Meanwhile, they are not sure if they prefer to catch keli (3.83±1.19) while fishing. The anglers were satisfied with all of the facilities provided by the management of the pay-fishing ponds, especially on the ‘toilet, surau and the pond’s parking lot’ (4.13±0.65). The findings of this research are useful to improve recreational fishing activities at the pay-fishing ponds in Serdang area, and in Malaysia in general.